PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN LAPTOP MEREK TOSHIBA (Studi pada Mahasiswa Fakultas Ekonomika dan Bisnis Unisbank Semarang) (Students' Journal of Economic and Management, 2015)
Toshiba is a world leader in high technology. The problem in this research is the shift in market share brand notebook toshiba is indicative of consumer distrust of the brand, quality products that are not durable and the perception of expensive prices. The aim of this study was to analyze the influence of brand image, product quality and price perception of the Toshiba brand laptop purchase decision on the students of the Faculty of Economics and Business Unisbank Semarang. Population in this research is the students of the Faculty of Economics and Business Unisbank Semarang. The sample in this study as many as 100 people. The sampling technique uses accidental sampling. The analytical tool used is multiple linear regression. Results of the analysis can be concluded that: Brand image has positive influence on purchase decisions. Product quality has positive influence on purchase decisions. Perception price positive influence on purchasing decisions. The most dominant variable in influencing the purchasing decision is the quality of the product, followed by brand image and perception of price. Keywords: brand image, product quality, price perception and purchasing decisions.